Racial and Ethnic Disparities in Patients' Experience With Skilled Home Health Care Services. (December 2015) - Smith, Laura M.; Anderson, Wayne L.; Kenyon, Anne; Kinyara, Elizabeth; With, Sarah K.; Teichman, Lori; Dean-Whittaker, Debra; Goldstein, Elizabeth
Racial and ethnic disparities are found in many health care settings; however, there is little prior research on such disparities among patients receiving home health care services. This study used 2012 Home Health Care CAHPS ® data to identify any overall patient-level disparities in self-reported experience of care and to decompose these disparities according to whether they result from within-agency versus between-agency differences. Although patient experience of care ratings were high across all groups, the study identified consistently lower ratings for all minority groups on two of three Home Health Care CAHPS measures, with Asians reporting the greatest disparities. Three quarters of disparities were found to be within-agency disparities, which were primarily related to care processes and provider/patient communications rather than to specific health care services received. Despite high ratings in general, home health agencies may need to focus on cultural competency initiatives to address racial and ethnic disparities within their agencies.